Effect of Combination Therapy of Multiple Antihypertensive Drugs with Diuretics on Kidney Function in Congestive Heart Failure Patients - Rahmi Yosmar; Surya Dharma; Annisa Nurbuana Putri (Journal of Health Economic and Policy Research (JHEPR), 2023)
Congestive heart failure is the inability of the heart to pump adequate blood that can cause kidney problems. Congestive heart failure causes fluid buildup or edema. This can be overcome by administering diuretics that act on the kidneys by removing fluid retention. This study aims to determine patients' sociodemographic and clinical characteristics and evaluate kidney function in patients receiving antihypertensive combination therapy with diuretics. Method: This research is observational, with a cohort study design and a retrospective approach. Result: The number of samples that met the criteria were 52 patients with sociodemographic characteristics, which were dominated by women as much as 61.5%, aged over 65 years 44.2%, high school education level 55.8%, and worked as IRT (Housewife) 48.1 %. While the clinical characteristics of patients based on length of stay were the most three days 36.5%, and 40-47 kg body weight 19.2%. Of the 52 patients receiving antihypertensive combination therapy with diuretics, 25% (13 people) had normal kidney function, 40% (21 people) had mild kidney impairment, and 35% (18 people) had moderate kidney impairment. Conclusion: based on statistical analysis, antihypertensive drugs with diuretics had no significant effect on kidney function.